Third Year Plan Summary of Draft Outline - Ministry of Information and Broadcasting Government Of India (Ministry of Information and Broadcasting Government Of India, 1960)
The Third Five-Year Plan of India (1961–66) outlines a comprehensive strategy for economic and social development under a socialist pattern of society, emphasizing public sector growth while acknowledging private enterprise. The plan targets over 5% annual national income growth, food self-sufficiency, expansion of basic industries, and creation of 8 million non-agricultural jobs. Key allocations include ₹6,200 crores to the public sector, ₹2,500 crores for industry and minerals, ₹975 crores for power, and ₹1,450 crores for transport infrastructure. Social services, including education and health, receive ₹1,250 crores, with a focus on compulsory education and health unit expansion. The plan also emphasizes technical training, aiming to produce 200,000 skilled craftsmen. By integrating economic growth with social welfare, the plan seeks to promote equitable development and national self-reliance.
Ministry of Information and Broadcasting Government Of India
Keywords: Third Five-Year Plan; Economic Growth; Public Sector; Agricultural Self-Sufficiency; Industrial Expansion; Employment Creation; Income Redistribution; Infrastructure Development; Social Services; Manpower Training